Case report: a rare case of Hunter syndrome (type II mucopolysaccharidosis) in a girl - A. N. Semyachkina; E. Y. Voskoboeva; E. Y. Zakharova; E. A. Nikolaeva; I. V. Kanivets; A. D. Kolotii; G. V. Baydakova; M. N. Kharabadze; R. G. Kuramagomedova; N. V. Melnikova (BMC, 2019)
Abstract Background Hunter syndrome (mucopolysaccharidosis type II) is a recessive X-linked disorder due to mutations in the iduronate 2-sulfatase (IDS) gene. The IDS gene encodes a lysosomal enzyme, iduronate 2-sulfatase. The disease occurs almost exclusively in males. However, in the literature, 12 cases of the disease in females are known due to structural anomalies, a non-random chromosome X inactivation or chromosome X monosomy. The purpose of this article is to demonstrate a rare case of Hunter syndrome in a girl caused by a mutation in the IDS gene inherited from the mother and the presence of chromosome X of paternal origin, partially deleted in the long arm region - 46,X,del(X)(q22.1). Case presentation Girl M., 4 years old, entered the hospital with growth retardation, pain in the lower limbs, and joint stiffness, noted from the age of 18 months. After the karyotype analysis, which revealed a partial deletion of the long arm of chromosome X - 46, X, del (X) (q 22.1), Turner syndrome was diagnosed. However, due to the hurler-like facial phenotype, Hurler syndrome or type I mucopolysaccharidosis (MPS) was suspected. The study of lysosomal enzymes showed normal alpha-L-iduronidase activity and a sharp decrease in the activity of iduronate sulfatase in the blood: 0.001 μM/l/h, at a rate of 2.5-50 μM/l/h. Molecular genetic analysis revealed a hemizygous deletion in the IDS gene, which was not registered in the international Human Gene Mutation Database (HGMD) professional. This deletion was not detected in the girl's father, but was detected in her mother in the heterozygous state. Conclusions Thus, the girl confirmed comorbidity - Turner syndrome with a partial deletion of the long arm of chromosome X of paternal origin, affecting the Xq28 region (localization of the IDS gene), and Hunter syndrome due to a deletion of the IDS gene inherited from the mother. The structural defect of chromosome X in the girl confirmed the hemizygous state due to the mutation in the IDS gene, which has led to the formation of the clinical phenotype of Hunter syndrome.